Kenaf-aramid fibre-reinforced polyvinyl butyral hybrid composites for military helmet - Salman, Suhad Dawood (2017)
Traditionally, the helmet shell has been used to provide protection against ballistic threats to reduce head injuries and fatalities. Owing to the high cost of aramid fibres and the necessity for environmentally friendly alternatives, a portion of aramid was replaced by plain woven kenaf fibre, with different arrangements and thicknesses, without jeopardising the stringent requirements demanded by military helmet specifications. Furthermore, novel helmets have been produced and tested with a specific threat level (National Institute of Justice standards, NIJ), in order to reduce the dependency on the ballistic resistance components. Experiments were conducted with more focus on the estimation the NIJ level, ballistic limit (V50), maximum energy absorption, hybrid failure mechanism and trauma depth. The NIJ results showed that the laminated hybrids with kenaf fibres passed the 4th level (IIIA) up to four layers, using 9 mm FMJ ammunition. While laminated hybrid shell with six kenaf layers and above passed the 3th level (II). Hybrid with 16 aramid/3 kenaf laminated composite recorded the highest V50 among other hybrids composite, 633.7 m/s. The arrangement of fibre layers was also found to affect the ballistic performance of the hybrid composites significantly, placing woven kenaf alternate with aramid fabric layers provided a lower ballistic limit velocity than placing woven kenaf together and aramid layers separately for the same hybrid volume and thickness. The laminated composites were subjected to physical, tensile, flexural, drop weight impact and quasi-static penetration tests. The laminates composed of 19 layers and were fabricated using different number and configurations of plain woven kenaf and aramid layers reinforced Polyvinyl Butyral (PVB) film, by the hot press technique. The experimental results demonstrated that the overall mechanical properties of the kenaf/aramid hybrid were dependent on the kenaf fibre content. Hybrid with 17 aramid/2 kenaf layers exhibited the best mechanical properties compared to other hybrid composites. Generally, the results suggested that stacking sequence, thickness and kenaf fibre content significantly influenced the mechanical and ballistic performance. It can be concluded from the research that it is possible to reduce the amount of aramid fibres in conventional PASGT (Personal Armour System Ground Troops) shell by 21% by hybridizing aramid with kenaf fibre, thus providing a lower cost alternative that is environmentally friendly.